Penile Fracture- Outcome of Early Surgical Intervention - Masroor Hussain Malik,Zein-el-Amir, Muhammad Ali Shahiman,Ashfaq Ahmed, Muhammad Afzal Farooqi , (Journal of Rawalpindi Medical College, 2012)
Background To evaluate the clinical features, treatment options and outcome of different modalities of treatment, for penile fracture . Methods: In this descriptive study cases of penile fracture were enrolled on the basis of history, physical examination. Cause of fracture and extent of urethral damage was assessed. In patients who underwent surgical exploration, urethral tear was repaired. In patients with complete urethral transection end to end anastomosis was performed. Results: Out of 32 cases, 27 (84.4%) underwent surgical exploration, 5 were conservatively managed because of refusal from surgery. Surgery was performed in 27 patients (all had fractures). Majority(70.4%) had tear of tunica albuginea of Rt. Corpus cavernosum. In 06 (22.22%) cases associated urethral injury was found. In 02 cases, with complete urethral transection, end-to-end anstomosis was performed and good voiding function (urine flow rates 22-24ml/sec mean 23.4ml/sec) was achieved. All 27 cases achieved normal curvature and erectile function. Among 5 patients submitted to conservative management, 2 developed curvature abnormality but with satisfactory erection, one patient has mildly painful erection requiring analgesics before sexual activity and one patient has residual penile mass unable to perform sexual activity. Conclusions: Penile fracture is a urologic emergency requiring clinical diagnosis and early surgical management to avoid complications related to erectile dysfunction.